Management of Sclerotinia Blight of Peanut with the Biological Control Agent Coniothyrium minitans - Partridge, D E (Plant disease, 2006)
Sclerotinia blight, caused by Sclerotinia minor, is an important disease of peanut in North Carolina. The effectiveness of Coniothyrium minitans, a mycoparasite of sclerotia of Sclerotinia spp., was studied in a 5-year field experiment and in eight short-term experiments in northeastern North Carolina. The 5-year experiment was initiated in November 1999 to evaluate the effectiveness of repeated soil applications of C. minitans (commercial formulation, Contans WG) at 2 and 4 kg ha-1 in reducing Sclerotinia blight. In addition, individual commercial peanut fields were selected in 2001 and 2002 to evaluate a single application of C. minitans at 4 kg ha-1. No differences were found between the 2 and 4 kg ha-1 rates of C. minitans in reducing Sclerotinia blight. In 2002, there was less disease in plots receiving applications of C. minitans for either 1 or 3 years compared with the nontreated control; whereas, in 2003, C. minitans applications for 1, 2, or 3 years reduced disease and the number of sclerotia isolated from soil. A single application of C. minitans reduced sclerotia in only two of the eight short-term experiments. The integration of consecutive years of soil applications of C. minitans at 2 kg ha-1 with moderately resistant cultivars and fungicide applications may aid in the management of Sclerotinia blight in peanut